2018
DOI: 10.1007/s00248-018-1195-z
|View full text |Cite
|
Sign up to set email alerts
|

Eco-epidemiology of Novel Bartonella Genotypes from Parasitic Flies of Insectivorous Bats

Abstract: Bats are important zoonotic reservoirs for many pathogens worldwide. Although their highly specialized ectoparasites, bat flies (Diptera: Hippoboscoidea), can transmit Bartonella bacteria including human pathogens, their eco-epidemiology is unexplored. Here, we analyzed the prevalence and diversity of Bartonella strains sampled from 10 bat fly species from 14 European bat species. We found high prevalence of Bartonella spp. in most bat fly species with wide geographical distribution. Bat species explained most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…In addition, ectoparasites were sampled during inspection of dead bats collected in the Netherlands between 1993 and 2011 and stored in the Naturalis Biodiversity Center, Leiden, the Netherlands. Bat flies from Hungary and Romania derived from a study by Sándor et al (2018). All bats were morphologically identified to the species level.…”
Section: Study Sites and Specimen Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ectoparasites were sampled during inspection of dead bats collected in the Netherlands between 1993 and 2011 and stored in the Naturalis Biodiversity Center, Leiden, the Netherlands. Bat flies from Hungary and Romania derived from a study by Sándor et al (2018). All bats were morphologically identified to the species level.…”
Section: Study Sites and Specimen Collectionmentioning
confidence: 99%
“…myotis, My. nattereri, R. blasii, R. euryale, R. ferrumequinum, and R. mehelyi) derived from a study by Sándor et al (2018) in Hungary and Romania were included.…”
Section: Bat Ectoparasitesmentioning
confidence: 99%
“…Reports of Bartonella spp. infections are known from blood of bats (Judson et al 2015, Han et al 2017, Urushadze et al 2017), from tissues (Bai et al 2017, Stuckey et al 2017) and from their associated ectoparasites (Morse et al 2012, Davoust et al 2016, Sándor et al 2018, Hornok et al 2019). In our study this pathogen group was found in low proportions, in two samples (2 out of 10, 20%), but the PCR targeting the ITS gene of Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Bats are the source for many diseases, like for example viruses causing rabies, EBOLA, severe acute respiratory syndrome, and Middle East respiratory syndrome all likely originating in bats (Hayman 2019). Moreover, bats are reservoirs of highly diverse pathogenic bacterial groups, without showing any apparent signs of disease ( Bartonella spp., Corduneanu et al 2018 or haemoplasmas - Holz et al 2019). Bats are able to sustain an energetically demanding lifestyle attained through high basal metabolic rate (active flight).…”
Section: Introductionmentioning
confidence: 99%
“…Bat flies are vectors of the haemosporidian Polychromophilus spp., a blood parasite closely related to Plasmodium, as well as suspected vectors of other pathogens such as the gram-negative bacteria Bartonella spp. [33][34][35]. Little is known about the interaction between pathogens and bat flies.…”
Section: Introductionmentioning
confidence: 99%